Down-regulation of transforming growth factor beta-2 expression is associated with the reduction of cyclosporin induced gingival overgrowth in rats treated with roxithromycin: an experimental study - Aarestrup Fernando; Vieira Beatriz; Bastos Marcus; Condé Simone (BMC, 2009)
Abstract Background Gingival overgrowth (GO) is a common side effect of the chronic use of cyclosporine (CsA), an immunosuppressant widely used to prevent rejection in transplant patients. Recent studies have reported elevated levels of specific cytokines in gingival overgrowth tissue, particularly TGF-beta, suggesting that this growth factor plays a role in the accumulation of extracellular matrix materials. The effectiveness of azithromycin, a macrolide antibiotic, in the regression of this undesirable side effect has also been demonstrated. Methods In this study, we created an experimental model for assessing the therapeutic effect of roxithromycin in GO and the expression of transforming growth factor beta (TGF-beta2) through immunohistochemistry. We used four groups of rats totaling 32 individuals. GO was induced during five weeks and drug treatment was given on the 6th week as follows: group 1 received saline; group 2 received CsA and was treated with saline on the 6th week; group 3 received CsA and, on the 6th week, ampicilin; and group 4 received CsA during 5 weeks and, on the 6th week, was treated with roxithromycin. Results The results demonstrated that roxithromycin treatment was effective in reducing cyclosporine-induced GO in rats. Both epithelial and connective tissue showed a decrease in thickness and a significant reduction in TGF-beta2 expression, with a lower number of fibroblasts, reduction in fibrotic areas and decrease in inflammatory infiltrate. Conclusion The present data suggest that the down-regulation of TGF-beta2 expression may be an important mechanism of action by which roxithromycin inhibits GO.